Combination of bevacizumab, irinotecan, and temozolomide for refractory or relapsed neuroblastoma: Results of a phase II study. Issue 8 (23rd January 2017) - Modak, Shakeel; Kushner, Brian H.; Basu, Ellen; Roberts, Stephen S.; Cheung, Nai‐Kong V.
Abstract: Background: The rationale for studying the combination of bevacizumab, irinotecan, and temozolomide (BIT) in neuroblastoma (NB) is based on the following: (i) vascular endothelial growth factor (VEGF) expression is associated with an aggressive phenotype, (ii) anti‐VEGF antibody bevacizumab enhances irinotecan‐mediated suppression of NB xenografts, (iii) bevacizumab safety has been established in pediatric phase I studies, and (iv) irinotecan + temozolomide (IT) is a standard salvage chemotherapy. Procedure: We conducted a phase II study of BIT in patients with measurable/evaluable refractory or relapsed high‐risk NB (www.clinicaltrials.gov, NCT01114555). Each cycle consisted of bevacizumab (15 mg/kg intravenously [IV]) on days 1 and 15 plus irinotecan (50 mg/m 2 /day IV) and temozolomide (150 mg/m 2 /day orally) on days 4–8. Patients could have previously received, but not relapsed on, IT. An early stopping rule mandated continuing therapy only if more than five patients of 27 evaluable patients achieved partial response (PR) or complete response (CR) after four cycles. Results: Thirty‐three heavily pretreated patients (nine primary refractory; 24 relapsed) received one to eight cycles of BIT. Toxicities were expected and transient. Grade 4 toxicities were neutropenia (30%) and thrombocytopenia (24%). Grade 3 toxicities included hepatic transaminitis (15%), proteinuria (9%), and diarrhea (3%). Overall responses were as follows: three CR (all in prior IT‐treated patients), 18 no response, and 12 progressive disease. Only one of 23 patients assessable for the early stopping rule regarding efficacy achieved PR/CR, so patient accrual was discontinued. Median progression‐free survival and overall survival was 7.7 ± 1.7 and 31.5 ± 5.6 months, respectively; all patients continued anti‐NB therapy post‐BIT. Conclusions: BIT was well tolerated, but the addition of bevacizumab did not improve response rates in resistant NB compared to historical data for IT.